Large enhanced conversion efficiency of perovskite solar cells by CsBr doping - Zhang, Li-Ying; Zhang, Yong; Guan, Wei-Bao; Wang, Ke-Fan; Cheng, Zhen-Xiang; Wang, Yuan-Xu (Journal of materials science, 2017)
Perovskite solar cells single-doped with Br − or Cs + ions have been proved to be an effective approach to improve their efficiency and stability. In our work, we took advantage of co-doping with Br − and Cs + . At our studied doping levels from CH 3 NH 3 I:PbI 2 :CsBr = 1:1:0 ( x = 0) to 0.85:1:0.15 ( x = 0.15), CsBr doping does not introduce any detectable impurity, and the crystal grains grow larger with increasing CsBr doping level. Furthermore, when the CsBr doping level is less than x = 0.1, it can progressively enhance the optical absorption of the perovskite film, although the absorption begins to decrease when the doping level rises above x = 0.1. X-ray photoelectron spectroscopy measurements show that Br − has successfully replaced I − and bonds with Pb 2+ after CsBr doping. At the optimized doping level of x = 0.1, the incorporation of CsBr in the reaction system can improve the morphology of perovskite films and greatly enhance the efficiency from 9.8% for undoped sample to 13.6%, better than single Br − or Cs + doping. Our result shows that CsBr doping is an effective method to enhance the efficiency of perovskite solar cells.